Effect of trans-theoretical model-based health education on self-management behaviors of patients with systemic lupus erythematosus - HU Nie; LIU Yi; HUANG Xi; ZHU Jingjing; LEI Ying; XIONG Shiping; CHEN Bo; SHEN Duanduan (Yixue xinzhi zazhi, 2025)
Objective To investigate the effect of health education guided by the trans-theoretical model (TTM) on blood glucose management in patients with systemic lupus erythematosus (SLE). Methods SLE patients who were treated in Zhongnan Hospital of Wuhan University from January to June 2022 were selected as the research objects and divided into an experimental group (using health education under the guidance of TTM) and a control group (using routine health education). The intervention was implemented from July 2022 to December 2022. The baseline data of all patients were evaluated before the intervention, and the changes in blood glucose levels and self-management behavior of patients were observed after 1, 3, and 6 months of intervention. Results A total of 160 patients were included, 80 in each of the experimental group and the control group, and the baseline characteristics of the two groups were comparable. The glycosylated hemoglobin values of the experimental group were significantly lower than those of the control group at 1, 3, and 6 months after the intervention, and the difference was statistically significant (P